2013
DOI: 10.1017/s1041610213001762
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methylphenidate on attention in apathetic AD patients in a randomized, placebo-controlled trial

Abstract: Background Little is known about the effect of methylphenidate (MPH) on attention in Alzheimer’s disease (AD). MPH has shown to improve apathy in AD, and both apathy and attention have been related to dopaminergic function. The goal was to investigate MPH effects on attention in AD and assess the relationship between attention and apathy responses. Methods MPH (10mg PO twice daily) or placebo was administered for 6 weeks in a randomized, double-blind trial in mild-to-moderate AD outpatients with apathy (Neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…The study, 133 however, was not specifi cally designed to assess apathy (Level U). These few fi ndings in Parkinson's disease are in line with double-blind, placebo-controlled studies [134][135][136] in Alzheimer's disease The following proposed criteria represent the views of the authors. They are intended to guide clinicians in making a diagnosis of apathy and in identifying appropriate treatments.…”
Section: Treatment Of Apathy In Parkinson's Diseasementioning
confidence: 55%
“…The study, 133 however, was not specifi cally designed to assess apathy (Level U). These few fi ndings in Parkinson's disease are in line with double-blind, placebo-controlled studies [134][135][136] in Alzheimer's disease The following proposed criteria represent the views of the authors. They are intended to guide clinicians in making a diagnosis of apathy and in identifying appropriate treatments.…”
Section: Treatment Of Apathy In Parkinson's Diseasementioning
confidence: 55%
“…Unfortunately, few controlled trials target treatment of apathy in AD. One recent randomized placebo-controlled trial of methylphenidate for apathy in AD (ADMET) reported improvement in two out of three efficacy outcomes with a trend toward improved global cognition with minimal adverse events [ 81 - 83 ]. Few other uncontrolled trials, however, have also shown treatment effects with methylphenidate [ 84 , 85 ] and one with donepezil [ 86 ].…”
Section: Management Of Common Neuropsychiatric Syndromes In Alzheimermentioning
confidence: 99%
“…Methylphenidate may improve executive functioning by increasing norepinephrine and dopamine concentrations in the synaptic cleft [6]. While some studies in patients with dementia due to Alzheimer's disease (AD) have suggested an effect of methylphenidate on global cognition and on attention [7][8][9][10], other studies have not consistently supported the results [11]. In patients with VCI, only 1 small older open label longitudinal study in 15 patients with dementia found that methylphenidate slightly improved scores on the Mini-Mental State Examination (MMSE) [12].…”
Section: Introductionmentioning
confidence: 99%